Synthesis of Needle-like CoO Nanowires Decorated with Electrospun Carbon Nanofibers for High-Performance Flexible Supercapacitors - Xiang Zhang (Nanomaterials)
Needle-like CoO nanowires have been successfully synthesized by a facile hydrothermal process on an electrospun carbon nanofibers substrate. The as-prepared sample mesoporous CoO nanowires aligned vertically on the surface of carbon nanofibers and cross-linked with each other, producing loosely porous nanostructures. These hybrid composite electrodes exhibit a high specific capacitance of 1068.3 F g−1 at a scan rate of 5 mV s−1 and a good rate capability of 613.7 F g−1 at a scan rate of 60 mV s−1 in a three-electrode cell. The CoO NWs@CNF//CNT@CNF asymmetric device exhibits remarkable cycling stability and delivers a capacitance of 79.3 F/g with a capacitance retention of 92.1 % after 10,000 cycles. The asymmetric device delivers a high energy density of 37 Wh kg−1 with a power density of 0.8 kW kg−1 and a high power density of 16 kW kg−1 with an energy density of 23 Wh kg−1. This study demonstrated a promising strategy to enhance the electrochemical performance of flexible supercapacitors.